Improved silicon/PEDOT:PSS core/shell nanowire hetero-junction for organic–inorganic hybrid solar cells. (21st January 2019) - Lu, Wenhui; Chen, Qiyin; Peng, Yirang; Zhang, Shuai; Pang, Tao; Zhang, Tiansheng; Luo, Fangfang; Yan, Lei; Wang, Xingzhu
Abstract: In this work, we describe an improved silicon/organic conducting polymer (PEDOT:PSS) core/shell nanowire hetero-junction through increasing the work function of the PEDOT:PSS for organic–inorganic hybrid solar cells. The resultant devices exhibit an enhanced open-circuit voltage and power conversion efficiency. Through analysis of the dark current density versus voltage curves, the enhanced open-circuit voltage can be attributed to the lower reverse saturation current density, which is induced by the high work function PEDOT:PSS. These results provide an effective strategy for improving the open-circuit voltage and power conversion efficiency of silicon-based core/shell nanowire solar cells.